Antibiotic Resistance of Pseudomonas aeruginosa in Burns and Wounds in Baghdad and Al-Samawah City - Alaboudi, Mohammed Ali; Aljwaid, Seger Abdulkhadim Seger (Manajemen Pelayanan Kesehatan, 2024)
The most prevalent pathogen in nosocomial situations remains to be pseudomonas aeruginosa. High levels of resistance to several antibiotic classes are displayed by this bacterium. Thus, the purpose of this work is to examine the multidrug-resistant P. aeruginosa bacteria that have been isolated from wound and burn infections. From burn and wound, 69 P. aeruginosa isolates were obtained. Antibiotic susceptibility testing was carried out using the conventional Kirby-Bauer disk-diffusion test method. The antibiotic resistance rate ranged between (20.28–85.5) for 69 isolates of P. aeruginosa tested. The current study revealed that P. aeruginosa isolates that higher level of resistance to Gentamicin, Cefepime, Ceftazidime Ticarcillin, Aztreonam, and also appear high sensitive to Amikacin, Imipenem, Meropenem and Ciprofloxacin. Therefore, in order to implement successful empirical medicines throughout hospital settings, it is imperative to carry out molecular epidemiology research and antibiotic surveillance.